The Effects Of Endowment And Loss Aversion In Managerial Stock Option Valuation - Devers, Cynthia E.; Wiseman, Robert M.; Holmes, R. Michael (Academy of Management Journal, 2007)
*The two lead authors are listed alphabetically to acknowledge that they contributed equally to this study. All authors thank Duane Ireland, Fred Morgeson, John Wagner III, and Kenna S. Boyd for their helpful comments on previous versions of this paper. We also thank Associate Editor Amy Hillman and three anonymous reviewers whose insightful comments significantly improved the clarity of our arguments. In addition, Cynthia Devers and Michael Holmes